Burst of Breath : Indigenous Ritual Wind Instruments in Lowland South America. - Hill, Jonathan David, 1954-; Chaumeil, Jean-Pierre (UNP - Nebraska Paperback, 2011)
"The first in-depth, comparative, and interdisciplinary study of Indigenous Amazonian musical cultures, Burst of Breath showcases new research on the dynamic range of ritual power and social significance of various wind instruments—including flutes, trumpets, clarinets, and whistles—played in sacred rituals and ceremonies in Lowland South America. The editors provide a detailed overview of the historical significance, scientific classification, shamanic and cosmological associations, and changing social meanings of ritual wind instruments within Amazonian cultures. These essays present a wide perspective that goes beyond better-documented areas such as the Upper Xingu and northwest Amazon. Some of the authors explore the ways ritual wind instruments are used to introduce natural sounds into social contexts and to cross boundaries between verbal and nonverbal communication. Others look at how ritual wind instruments and their music enter into local definitions and negotiations of relations between men, women, kin, insiders, and outsiders. Closely considering these instruments in their many roles and contexts—in curing and purification, negotiating relations, connecting mythic ancestors and humans today—this volume reveals the power and complexity of the music at the heart of collective rituals across lowland South America." --